Water-solvable carbon dots derived from curcumin and citric acid with enhanced broad-spectrum antibacterial and antibiofilm activity. (March 2021) - Lu, Fang; Ma, Yurong; Wang, Huibo; Zhang, Mengling; Wang, Bo; Zhang, Yue; Huang, Hui; Liao, Fan; Liu, Yang; Kang, Zhenhui
Abstract: Multidrug-resistant bacterial infections are one of the most serious public health threats in the world, which bring an urgent need to discover novel antibiotics with enhanced broad-spectrum antibacterial activity. Curcumin, as a widely used natural product, has good anti-inflammatory and antioxidant properties; while, the bioavailability, bioactivity and antibacterial activity design are limited by its poor water-solubility. Here, to improve the bioactivity of curcumin, we show the fabrication of highly water-solvable carbon dots (CDs) by hydrothermal method from citric acid and curcumin. The CDs possess excellent broad-spectrum antibacterial activity and antibiofilm activity because they can do damage to the bacterial walls when they get into the bacteria. The bactericidal efficiency of CDs (375 μg/mL) achieves up to 100 % for Gram-negative bacteria ( Escherichia coli and Pseudomonas aeruginosa ). Additionally, for Gram-positive bacteria ( Staphylococcus aureus and Bacillus subtilis ), the bactericidal efficiency reaches 80 %. In addition, these CDs also can completely inhibit the formation of biofilm for the Gram-negative bacteria and the Gram-positive bacteria. This work has a significant meaning in studying new antibacterial nanomaterials derived from natural product and the treatment of infections.